Proses Pemecahan Masalah Matematis Siswa SMP Materi Bentuk Aljabar melalui Model Problem-Based Learning - Erni Maidiyah; Laila Sari; Anwar Anwar (Jurnal Peluang, 2019)
Problem-solving is one of the skills the students need to master when learning mathematics. Based on observations, researchers found that students' mathematical problem-solving skills are lacking because students prioritize the learning outcomes than understanding the process of solving a problem. One of the teacher's efforts to solve these problems is to apply a problem-based learning model. This study aimed to investigate the process of students' mathematical problem-solving skills based on Polya's theory. The research conducted was qualitative. The subjects were 2 out of 30 Year 7 students selected based on the test results and information from the teacher, the selected students are one high-ability student and one student low ability student. Data collection involved tests and interviews. The results showed that high ability students was able to solve problems based on the four stages of Polya, while the low ability student wasnot be able to do many process of Polya. Therefore, there is still a need for closer teacher attention towards the students.